Valence bonds in elongated boron clusters. Issue 13 (4th January 2018) - Arvanitidis, Athanasios G.; Lim, Kie Zen; Havenith, Remco W. A.; Ceulemans, Arnout
Abstract: A well‐defined class of planar or quasi‐planar elongated boron clusters, of type B 7 + 3 n q −, serves as a basis to identify the valence bond picture of delocalized boron networks. The origin of the series is the B 7 − cluster, which exhibits σ‐aromaticity. The cluster generating step is the repetitive expansion by three boron atoms in the direction of elongation. Specific electron counting rules are obtained for π‐bonding, peripheral σ‐bonding and multicenter inner σ‐bonding. A valence bond structure is introduced which explains the remarkable regularity in the bonding pattern. The analysis supports 4c‐2e bonds as an alternative to the common 3c‐2e bonds. The results are validated by symmetry induction and ab initio calculations. Abstract : A well‐defined class of planar or quasi‐planar boron clusters serves as basis to identify the valence bond picture of delocalized boron networks. The origin of the series is the B 7 − cluster, which exhibits σ‐aromaticity. Specific electron counting rules are obtained for π‐bonding, peripheral σ‐bonding and multicenter inner σ‐bonding. A valence bond structure is introduced to explain the remarkable regularity in bonding pattern. The analysis supports 4c‐2e bonds as an alternative to the common 3c‐2e bonds.